2005
DOI: 10.1016/j.eurpsy.2004.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake-related psychological distress and associated factors 4 years after the Parnitha earthquake in Greece

Abstract: Exposure to earthquakes has been associated with psychological distress and in particular the development of post-traumatic stress disorder (PTSD). Earthquake-related psychological distress can be longstanding. The present study involved 157 Greek survivors of the 1999 Parnitha earthquake assessed approximately 4 years after the earthquake. Assessments were based on the Traumatic Stress Symptom Checklist (TSSC). Using stringent calibrations for the estimation of symptom presence 25% of the survivors endorsed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 33 publications
2
37
1
Order By: Relevance
“…Following this natural disaster, earthquakes occurred in the towns of Kalamata in 1986 and Aegion in 1995, and the most recent earthquake occurred in Athens in 1999. Ten epidemiological studies were carried out using specific research methodologies and standardized instruments and questionnaires to explore the psychological=psychiatric consequences of these natural disasters on exposed populations (Trichopoulos et al, 1983;Mantonakis et al, 1990;Bergiannaki et al, 1990;Papadatos et al, 1990;Soldatos et al, 1989;Bergiannaki et al, 2003;Livanou et al, 2005;Kolaitis et al, 2003;Roussos et al, 2005;Groome & Soureti, 2004;Giannopoulo et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this natural disaster, earthquakes occurred in the towns of Kalamata in 1986 and Aegion in 1995, and the most recent earthquake occurred in Athens in 1999. Ten epidemiological studies were carried out using specific research methodologies and standardized instruments and questionnaires to explore the psychological=psychiatric consequences of these natural disasters on exposed populations (Trichopoulos et al, 1983;Mantonakis et al, 1990;Bergiannaki et al, 1990;Papadatos et al, 1990;Soldatos et al, 1989;Bergiannaki et al, 2003;Livanou et al, 2005;Kolaitis et al, 2003;Roussos et al, 2005;Groome & Soureti, 2004;Giannopoulo et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…All scientific publications related to the epidemiology of mental disorders as a result of earthquakes in Greece were reviewed (Trichopoulos et al, 1983;Mantonakis et al, 1990;Bergiannaki et al, 1990;Papadatos et al, 1990;Soldatos et al, 1989;Bergiannaki et al, 2003;Livanou et al, 2005;Kolaitis et al, 2003;Roussos et al, 2005;Groome & Soureti, 2004;Giannopoulou et al, 2006). Trauma and Natural Disaster 139 The review included the recording of specific parameters such as the intensity, year, and location of the earthquake, including the death toll; the author(s) of the research; the instruments and sampling used; and the major findings.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in Turkey and Greece showed that the prevalence of psychological distress was still high in victims 3-4 years after the respective earthquakes [4,5]. In the case of the Niigata-Chuetsu earthquake, such long-standing effects are also expected to be present among the residents of Kawaguchi Town.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of disaster management, resilience is most often studied at the community level (Ainuddin & Routray, 2012;Chen, Ferng, Wang, Wu, & Wang, 2008;Cutter, Ash, & Emrich, 2014;Felsenstein & Lichter, 2014;Frazier, Thompson, Dezzani, & Butsick, 2013;Kafle, 2012). In the context of disasters, individual resilience is the second most prevalent level of analysis and the one most often studied in the medical and psychological literature (cf., Chang & Taormina 2011;Eisenman et al, 2014;Livanou et al, 2005;Rodriguez-Llanes, Vos, & Guha-Sapir, 2013;Van der Velden, Wong, Boshuizen, & Grievink, 2013).…”
Section: Levels Of Analysismentioning
confidence: 99%